THE CONSEQUENCES OF METABOLIC SYNDROME, SEX AND AGE ON THE METABOLOME AND EPIGENOME MUTUAL REGULATION: THE EPIGENETIC DRIFT IN SEVERE OBESITY. (June 2022) - Pisoni, Serena; Maria, Anna; Blasio, Di; Gentilini, Davide; Calzari, Luciano; Marrachelli, Vannina G.; Morales, Jose Manuel; Monleón, Daniel
Abstract : Objective: Metabolic syndrome (MetS) is the principal pathological consequence of obesity. Metabolome dysfunctions lead to multi-organ failure and cardiovascular complications, especially in the elderly. The metabolome is the output of genes-environment interaction and the epigenetic modifications act as their linker. So, it is reasonable a possible interplay between metabolomics and epigenetics. MetS prevalence increases sharply with age, especially in women, reaching in postmenopause a comparable prevalence to men of the same age. Our preliminary metabolomics results suggest stable significant differences between sexes in the global metabolic profiles. So, the aim is to study the interactions between metabolome and epigenome in subjects over 54 years old presenting metabolically healthy obesity (MHO) or severe MetS (MetS.5) to obtain a pathophysiological characterization of the most fragile patients. Design and method: 96 subjects (48 cases MetS.5, 48 controls MHO; age 55–85) were selected from a cohort of 1350 adult subjects with extreme obesity (BMI> 40 kg/m2). MetS.5 indicated the presence of the 5 metabolic alterations according to the International Diabetes Federation (IDF) (2005). The cohort was extensively characterized for anthropometric and clinical outlines and NMR metabolomics profiles were previously measured. Global methylation levels were measured in serum using the Infinium MethylationEPIC BeadChip kit and specific statistical analyses were developed. Results: The global methylation levels between cases and controls didn't appear different, although the epigenetic drift appeared higher in controls, due to the presence on average of a greater number of stochastic epigenetic variations (SEVs). The biological age, reflected by epigenetic age, appeared to be higher, on average, in men over women of similar chronological age, regardless of the pathological state, even if the last worsened the outcome. Conclusions: The epigenetics results, joint to the metabolomic data, may supply innovative knowledge and specific biomarkers involved in physiological mechanisms in healthy obesity and its pathological condition MetS. The results of the present study could add information and introduce new targets and biomarkers for better clinical treatment, a reduction in the risk of mortality and a better quality of life of extreme MetS patients.